Metode Tahfizh Al-Qur`an untuk Anak-Anak pada Pesantren Yanbu'ul Qur’an Kudus Jawa Tengah - Bahruddin, AH.; Mujahidin, Endin (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
The world of children is a world of play, but at the same time the most good age (golden age) to perform rote, then the need for a mix of playing time and time memorizing, one among the many institutions that integrate it is Yanbu'ul Qur’an Kudus Central of Java. Formulation of the problem formulated in this research is how the concept of Tahfizh Qu’ran for children held at Yanbu'ul Qu’ran Kudus Central of Java, and how excellent methods Tahfidz Qur'an for children. This study is a qualitative research, with the approach of field research, the data source is the leadership, teachers and students in Yanbu'ul Qur’an, Kudus, Central of Java. In this study it was found that the method tahfizh for children can be done by methods Talaqi, Taqrir, Musyafahah, and Iqabi. Tahfizh barriers contained in the Qur’an is the lack of children and parents who lack confidence with existing systems in Pondok. The results of this study addressed that tahfizh Qur’an to children in schools Yanbu'ul Qur'an tahfizh program needs to be made in full 30 juz in six years with a minimum target of 5 juz each year, according to the results classify rote memorization, equip anah young tahfizh with a formal certificate, provide limited formal education materials that provide support to tahfizh, and always made whenever SAP in the process of doing Tahfizh. While excellent method tahfizh for children is to integrate the mind, body and soul which was then called the method Ahsani. The conclusion from this study is the concept tahfizh in boarding Yanbu'ul Qur'an is quite effective and there are several factors that become an obstacle in running tahfizh Qur'an that sometimes disrupt this process tahfizh activities in schools Yanbu'ul Quran, but ended up with a solution that is done by deliberation either by students or by involving their parents. Ahsani method is an excellent method for Tahfiz children. Keyword: Children, learning method, Quran memorizing